2002
DOI: 10.1021/ja025699i
|View full text |Cite
|
Sign up to set email alerts
|

An Unnatural Amino Acid that Induces β-Sheet Folding and Interaction in Peptides

Abstract: This paper introduces a unique amino acid that can readily be incorporated into peptides to make them fold into beta-sheetlike structures that dimerize through beta-sheet interactions. This new amino acid, Orn(i-PrCO-Hao), consists of an ornithine residue with the beta-strand-mimicking amino acid Hao [J. Am. Chem. Soc. 2000, 122, 7654-7661] attached to its side chain. When Orn(i-PrCO-Hao) is incorporated into a peptide, or appended to its N-terminus, the Hao group hydrogen bonds to the three subsequent residue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 13 publications
2
60
0
Order By: Relevance
“…Strong NOEs between the Thr and Val a protons in the Tr-ROESY spectra of unmixed 1 b and 1 c, similar to those we reported previously for peptide 1 a, [4] help establish the formation of homodimers. A strong NOE between the two different Val a protons of the new species formed upon mixing 1 b and 1 c confirms the formation of the heterodimer.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Strong NOEs between the Thr and Val a protons in the Tr-ROESY spectra of unmixed 1 b and 1 c, similar to those we reported previously for peptide 1 a, [4] help establish the formation of homodimers. A strong NOE between the two different Val a protons of the new species formed upon mixing 1 b and 1 c confirms the formation of the heterodimer.…”
supporting
confidence: 86%
“…[3] We had previously reported that peptides such as 1 a, which contain the amino acid Orn(iPrCO-Hao), fold into bsheetlike structures that dimerize through b-sheet interactions in organic solvents (Scheme 1). [4] In the present study, we chose to replace the valine and leucine residues of 1 a with threonine and valine in all possible orders: Thr-Val (1 b), ValThr (1 c), Thr-Thr (1 d), and Val-Val (1 e). We selected these residues with the expectation that Val would pair preferentially with Val, and that Thr would pair preferentially with Thr, through self-complementary noncovalent interactions and with the knowledge that these pairings frequently occur in the non-hydrogen-bonded rings of antiparallel b sheets.…”
mentioning
confidence: 99%
“…Hence, human Aβ1-40 is amphiphilic, meaning that possess both hydrophobic and hydrophilic groups, like surfactants (Soreghan et al, 1994;Ji et al, 1995;Bokvist et al, 2004). Many reagents have been developed to modulate the aggregation of Aβ peptide (Pallitto et al, 1999;Lowe et al, 2001;Nowick et al, 2002;Ban et al, 2004), and, surfactants belong to one important category of the reagents.…”
Section: Discussionmentioning
confidence: 99%
“…Structural elements such as the fibrillous -peptidic nanostructures 47, 79-80 64 , short turns [81][82][83][84] , and a three stranded sheet in organic solvent 85 are described among -peptide foldamers. Sheet-structures that were stabilized by macrocyclization and a non-peptidic template showed bioactivity [6][7][8][9][10][11][12] but only a few other bioactive strand or -sheet like structures are known.…”
Section: Mimicking -Sheets By Foldamersmentioning
confidence: 99%
“…[3][4][5] The mimicry of -sheets therefore requires further investigations, only a few sheet-like structures are known with biological activity. [6][7][8][9][10][11][12] Our goal was to establish design strategies for conformationally diverse -sheet folding systems by using -peptide foldamers based on a selected peptide participating in proteinprotein and membrane interactions. The antiangiogenic and antimicrobial peptide anginex was chosen as a model system, [13][14][15] which exhibits diverse structural features.…”
Section: Introduction and Aimsmentioning
confidence: 99%